Amenhotep III's Mansion of Millions of Years in Thebes (Luxor, Egypt): Submergence of high grounds by river floods and Nile sediments. (June 2019) - Toonen, W.H.J.; Graham, A.; Masson-Berghoff, A.; Peeters, J.; Winkels, T.G.; Pennington, B.T.; Hunter, M.A.; Strutt, K.D.; Barker, D.S.; Emery, V.L.; Sollars, L.; Sourouzian, H.
Abstract: New Kingdom royal cult temples in Thebes (Luxor, Egypt) are all located on the lower desert edge. Kom el-Hettân (Amenhotep III: reign 1391–1353 BCE, 18th Dynasty) is an exception, as it is located in the present Nile floodplain. Its anomalous position has puzzled Egyptologists, as has the termination of its use, which traditionally has been attributed to natural hazards such as flooding or earthquakes. Geoarchaeological analyses of the subsurface shows that Amenhotep III's temple was initially founded on a wadi fan that stood several metres above the contemporary surrounding floodplain landscape. The temple was fronted by a minor branch of the Nile, which connected the temple to the wider region, but the temple itself was relatively safe from the annual flood of the Nile. This geoarchaeological study comprised a coring programme to determine the c. 4000-yr landscape history of the local area. Chronological control was provided by the analysis of ceramic fragments recovered from within the sediments. This study shows that the New Kingdom period was, at least locally, characterised by extremely high sedimentation rates that caused a rapid rise of the floodplain and gradual submergence of the pre-existing high temple grounds. This is, however, not a plausible reason for the destruction of the temple, as frequent inundation did not begin until the temple was already out of use and largely dismantled. Highlights: Kom el-Hettân was founded on high grounds, out of reach of regular Nile floods. The anomalous position of the temple was highly symbolic as an emerging island. A nearby river branch offered direct connection with other sites in the region. Extremely high sedimentation rates occurred during the New Kingdom period. Flooding during the New Kingdom cannot be linked to the destruction of the temple.